Attitudes of Chinese residents toward sugar-sweetened beverage tax and their willingness to pay: a cross-sectional survey - Zhang, Xuanfei; Bai, Jinrui; Xian, Mengyao; Sun, Junmao; Xu, Haiquan (Frontiers in Nutrition, 2023)
Background: Excessive consumption of sugar-sweetened beverages (SSBs) is associated with increased risks of obesity and chronic diseases. To effectively control SSB consumption, several countries including Mexico, France, and the United Kingdom have implemented SSB taxes.However, research on SSB taxes in China is limited. Objective: To assess the attitudes of Chinese residents toward the SSB tax and their willingness to pay the tax. Methods: Data were collected through a questionnaire survey among 881 respondents. The generalized ordered logit regression model and marginal effect analysis were used to analyze Chinese participants' attitudes toward SSB tax and their willingness to pay it. Results: The average monthly expenditure on SSBs was 44.8 ± 45.3 Yuan (RMB)(6.95 ± 7.02), and 54.6% of residents supported the SSB tax; they were willing to pay, on average, 1.19 times the original price after additional tax. Age, physical exercise, self-rated health status, weight control plan, awareness of SSBs, children's consumption of SSBs, and proximity to the nearest SSB outlet significantly influenced attitudes toward tax. Notably, SSB awareness had the greatest effect on tax attitudes, with a 17% increase in the probability of supporting SSB tax for every one-level increase in SSB awareness among residents. Conclusions:Residents in China have attained a certain level of awareness of, support for, and willingness to pay SSB tax. However, promoting knowledge about the health effects of SSBs and conducting further research to evaluate the effect of SSB tax on obesity prevention in China is still essential.Currently, the consumption of sugar-sweetened beverages is on the rise in various countries(1). In China, the rising beverage consumption led to a significant increase in beverage production, with sugar-sweetened beverages (SSBs) accounting for more than half of the Chinese beverage market (2).However, excessive SSB consumption is associated with increased risks of obesity, type 2 diabetes, cardiovascular disease, and other chronic diseases (3-5). Furthermore, SSB intake is linked to a T 删除[z]: he 删除[z]: